How do Muslim-Majority Countries Respond to Islamic Political Parties? Research Trend Studies and Theme Mapping - Hasse Jubba; Paisal Akbar; Achmad Nurmandi; Andi Luhur Prianto; Arifeen Yama; Mohammad Eisa Ruhullah (Otoritas : Jurnal Ilmu Pemerintahan, 2022)
This study aims to explore Islamic political parties in major Islamic countries. Previous studies have examined Islamic Political Parties with various topics accompanied by different focuses. However, no research has contributed to mapping the extent of the trend in the study of Islamic political parties. The breadth of space to examine the phenomenon of Islamic political parties offers an excellent opportunity for further researchers to re-examine this issue. To bridge this, trend studies and mapping of problems and themes were carried out. This study uses qualitative methods to analyze working texts on publications related to Islamic Political Parties. Research data is mined from the Scopus academic database using a search strategy to generate data relevant to the problem to be studied. In processing the mined data, we use Qualitative Data Analysis (QDA) software, Nvivo12 Plus. The results of an in-depth analysis of a collection of academic manuscripts mined from the Scopus academy database for two decades (2001-2021) yielded 171 documents for further study. The data analysis findings show that the intensity of documents in each country is different, which can then be further classified based on the type of document, subject area, author with the highest number of records, and distribution of affiliations and publishers. The level of document intensity in each country has been shown, with Turkey being the country that contributed the most documents, followed by Indonesia, Malaysia, and India. The dominant issues and themes of each country have also been identified.